Moments in Time : On Narration and Slowness - Gaensheimer, Susanne; Friedel, Helmut; Gaertner, Matthias; Netta, Irene; Tarantino, Michael; Wilmes, Ulrich; Lenbachhaus, München (Ostfildern : Hatje Cantz Verlag, 1999)
Coleman, James ; Dean, Tacita ; Douglas, Stan ; Gordon, Douglas ; McQueen, Steve ; Nauman, Bruce ; Trockel, Rosemarie ; Viola, Bill
Moments in Time, Lenbachhaus Kunstbau Munich, Munich, April 28 - June 13 1999
kunstcatalogus